Students’ Perception using Twitter (X) Account Auto-Base Englishfess to Learn English Grammar - Syafar, Miftahul Jannah; Tahir, Muh.; Sofyan, Ryan Rayhana (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This study aims to describe the perception of the auto-based Twitter account Englishfess (X) in learning English grammar. The design of this research method uses a descriptive qualitative approach. Online in-depth interviews and document analysis are used in data collection. The researcher took participants from followers of the Englishfess account who are high school students in Indonesia with an age range of 15-18 years. The results of this study found that students have a positive perception of the use of the auto-based Englishfess account. Students believe that they get many benefits from using Twitter (X) in learning English grammar, such as improving students understanding of grammar concepts, increasing their grammar awareness, and making it easier to communicate with other users in learning English grammar. This study also found a positive perception from students that posts or tweets from the auto-based Englishfess account are quite accurate and of high quality in presenting grammar discussions, the diversity of content provided, and encouraging students' motivation to learn grammar on social media.